2004
DOI: 10.1524/ncrs.2004.219.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of diethyl 2-(dibenzoylmethyl)-3-(triphenylphosphoranylidene) succinate, C41H37O6P

Abstract: C41H37O6P, triclinic, P1̅ (no. 2), a = 11.128(5) Å, b = 12.548(5) Å, c = 13.420(5) Å, α = 87.523(5)°, β = 84.819(5)°, γ = 64.188(5)°, V = 1680.0 Å3, Z = 2, Rgt(F) = 0.058, wRref(F2) = 0.148, T = 173 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In the investigated crystal, the chiral atom C(22) (Fig. 1 The molecular geometry observed in 5a corresponds well with the knowledge on stabilized phosphonium ylides [1,9]. The values of P-C(19) Table 2 and compare with the unaffected C(22)-C(23) distance and the whole (C(23)=O(3))-O4-C24 ester group).…”
Section: Description Of the Crystal Structure Of 5asupporting
confidence: 83%
See 3 more Smart Citations
“…In the investigated crystal, the chiral atom C(22) (Fig. 1 The molecular geometry observed in 5a corresponds well with the knowledge on stabilized phosphonium ylides [1,9]. The values of P-C(19) Table 2 and compare with the unaffected C(22)-C(23) distance and the whole (C(23)=O(3))-O4-C24 ester group).…”
Section: Description Of the Crystal Structure Of 5asupporting
confidence: 83%
“…Consequently, the two rotamers (5E E E and 5Z Z Z in Scheme 1, with different O(1) to P orientation) may be expected and were shown indeed by NMR to exist in equilibrium in CDCl 3 solution. However, the X-ray data demonstrated that, in the solid state, this orientation may be opposite even in compounds of highly related structures [9,10]. The ylide molecules in 5a and in the crystal of analogous compound described recently (ethyl ester of a phenyl derivative [9]) adopt different orientation of the carbonyl O(1) atom with respect to the P atom.…”
Section: Description Of the Crystal Structure Of 5amentioning
confidence: 99%
See 2 more Smart Citations
“…Yield: 0.286 g (97 %). -IR (neat): ν = 2984, 1723, 1653,prepared using the branch tube method [12] with light petroleum ether at 60 • C during 24 h. The colorless crystals were filtered off, washed with cold light petroleum ether (3 mL) and dried at r. t.…”
Section: General Proceduresmentioning
confidence: 99%